Ultrasound-Assisted Synthesis and Biological Activity of Oximes - YUYE, YU (Asian Journal of Chemistry, 2010)
The conversion of alicyclic, aliphatic carbonyl compounds and aromatic aldehydes into the corresponding oximes was achieved by ultrasound irradiation in presence of hydroxylamine hydrochloride and potassium carbonate. The biological test showed that the synthesized compound has weak fungicidal activity. The structures of compounds were characterized by melting points, 1H NMR and IR.